Long-Term Surgical Outcomes of Carotid Body Tumors With Pathological Fibrosis: A Cohort Study - Tang, Hanfei; Jiang, Xiaolang; Xue, Song; Fu, Weiguo; Tang, Xiao; Guo, Daqiao (Frontiers in Oncology, 2021)
Objective: To compare the surgical outcomes of carotid body tumor (CBT) with or without pathological fibrosis, and to evaluate the associated factors of fibrous CBT (FCBT) Materials and Methods: Paraffin-embedded tissues of 236 patients with unilateral CBTs at our center were retrospectively reviewed from January 2008 to May 2020. Based on the pathologic features, CBTs were divided into FCBT and conventional CBT (CCBT) groups. The clinical data and surgical outcomes of the two groups were compared. Results: Out of 236 patients, 53 had FCBT and 183 had CCBT. Comparatively, FCBTs showed higher vascular invasion (24.53%), marked pleomorphism (22.64%), internal carotid artery reconstruction (37.74%), estimated blood loss (559.62 cm3), and postoperative cranial nerve injury (CNI) (49.06%), with lower 10-year recurrence- (89.2%) and major adverse event-free survival (87.3%). CNI was correlated with the Shamblin grade; major adverse events and CNI were both correlated with pathological fibrosis. Conclusion: Compared with CCBT, FCBT is prone to increased recurrence, metastasis, major adverse events, and CNI risk. Early surgical resection, routine excision of surrounding abnormal lymph nodes, and closer clinical surveillance in FCBT patients are recommended.